Iontophoretic delivery of dexamethasone phosphate for non-infectious, non-necrotising anterior scleritis, dose-finding clinical trial. Issue 8 (17th April 2018) - O'Neil, Erin C; Huang, Jiayan; Suhler, Eric B; Dunn Jr, James P; Perez, Victor L; Gritz, David C; McWilliams, Kathy; Peskin, Ellen; Ying, Gui-shuang; Bunya, Vatinee Y; Maguire, Maureen G; Kempen, John H
Abstract : Abstract: Currently available treatment options for non-infectious scleritis, including non-steroidal anti-inflammatory drugs, systemic corticosteroids and immunosuppressive therapies, have both efficacy and side effect limitations. Iontophoretic delivery of corticosteroids has been demonstrated to be effective for anterior uveitis and represents a potential new approach to scleritis therapy. We hypothesised that iontophoretic delivery would provide effective and precise medication delivery to the sclera, while limiting systemic exposure and side effects. This first-in-human randomised, double-masked, dose-escalating study of iontophoretic administration of dexamethasone phosphate for scleritis suggests the treatment to be well tolerated and safe (within the limitations of the 18 patients sample size). There was a suggestion of efficacy in the lowest (1.2 mA/min at 0.4 mA) dose group (corresponding to the superficial location of scleritis compared with anterior uveitis), with 5/7 eyes meeting the primary efficacy outcome within 28 days. Our results suggest iontophoretic delivery of corticosteroids is a promising potential treatment for scleritis, with favourable safety and preliminary efficacy results in this phase 1 trial. Trial registration number: NCT01059955 .